Layered lithium-rich manganese oxide positive electrode material with effective improved rate performance and preparation method and application thereof
By doping the precursor of LiCoO2 into the layered lithium-rich manganese oxide cathode material, the problems of poor rate performance and cycle stability are solved, and efficient charge and discharge performance at high rates and large currents are achieved.
Patent Information
- Application Number
- CN202010707220.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-07-21
AI Technical Summary
The layered lithium-rich manganese oxide positive electrode material has poor rate performance, poor cycle stability and high current charge and discharge performance, which limits its application in lithium-ion batteries.
In the preparation process of the precursor of the layered lithium-rich manganese oxide cathode material for lithium-ion batteries, doping can provide the raw material precursor of LiCoO2, and the modified layered lithium-rich manganese oxide cathode material is obtained through high-temperature heat treatment.
By increasing the composition of LiCoO2, the electronic conductivity of the lithium-rich manganese cathode material is increased, thereby significantly improving its rate performance and high-current charge and discharge performance, achieving capacity maintenance and rapid charge and discharge at high rates.
Smart Images

Figure CN111732125B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of positive electrode materials for lithium-ion batteries, and in particular to a layered lithium-rich manganese oxide positive electrode material that can effectively improve rate performance, and a preparation method and application thereof. Background Art
[0002] As people's demand for energy grows and their understanding of the importance of sustainable social and economic development deepens, lithium-ion batteries, which are characterized by high energy efficiency and green environmental protection, are gaining more and more attention. Applications such as new energy storage, electric vehicles, and smart grids have put forward higher requirements for the energy density, cycle life, power density, safety, cost, and environmental friendliness of lithium-ion batteries. 1 / 3 Co 1 / 3 Mn 1 / 3 The specific capacity of layered oxide positive electrode materials such as O2 is always limited to less than 150 mAh / g. The theoretical specific capacity of spinel structure LiMn2O4 positive electrode materials and polyanion type LiFePO4 positive electrode materials are only 148 mAh / g and 170 mAh / g respectively, and the actual capacity is even lower, far from meeting the performance requirements of high specific energy density lithium-ion batteries for positive electrode materials. Therefore, positive electrode materials have become a bottleneck for further improving the performance of lithium-ion batteries. Layered lithium-rich manganese oxide positive electrode materials have attracted the attention of scientists due to their unique advantages:
[0003] (a) High discharge capacity: The first discharge specific capacity at room temperature is greater than 280 mAh / g, which is much greater than 140 mAh / g of LiCoO2 and 150 mAh / g of LiFePO4;
[0004] (b) Moderate average voltage: The average discharge voltage is 3.6 volts, which is within the current safe voltage range of organic electrolytes (electrolyte safety voltage window 0 to 5 volts);
[0005] (c) High mass-to-energy density: its energy density is greater than 1000 Wh / kg;
[0006] (d) Low cost: The Mn element in the layered lithium-rich manganese oxide replaces a large amount of expensive metal elements such as Co and Ni in the ternary material, greatly reducing the cost of the material.
[0007] (e) Simple synthesis and electrode preparation process: Layered lithium-rich manganese oxide positive electrode materials can be synthesized by simple solid-phase ball milling, liquid-phase coprecipitation, spray pyrolysis and other methods suitable for large-scale production, and the heat treatment process is simple, only requiring heat treatment at 800 to 900 degrees Celsius in air, and does not require atmosphere protection like LiFePO4. In the process of preparing the pole piece, there is no need to consider the oxidation of the active material, which greatly reduces the unpredictability of the pole piece in the preparation process.
[0008] However, the poor cycle stability and rate performance of layered lithium-rich manganese oxide positive electrode materials, as well as low first coulombic efficiency, seriously restrict their practical application. The layered lithium-rich manganese oxide positive electrode materials have poor rate performance, with a significant reduction in specific capacity and reduced cycle retention during high current charge and discharge. This is mainly due to the insulating properties of Li2MnO3, which leads to its very low electronic conductivity, and its large interface impedance also leads to poor rate performance. In addition, the poor kinetics of the Mn element and the sluggish kinetics of anion redox also contribute to the poor rate performance of layered lithium-rich manganese oxide positive electrode materials. Studies have reported that the electronic conduction properties of layered lithium-rich manganese oxides are usually improved by coating conductive carbon materials such as super-p, acetylene black, graphene, etc., and the ion conduction properties are improved by coating ion conductors, Al2O3, TiO2, Li4Mn5O12, etc. However, these coating methods can only improve the overall performance of the electrode and cannot change the intrinsic properties of lithium-rich manganese. Therefore, some studies have also adopted methods such as reducing the content of Li2MnO3 components and using ion doping / substitution methods to improve the intrinsic conductivity of lithium-rich manganese and improve its rate performance. However, doping modification will reduce the electrochemical capacity of the electrode material, and its modification effect is not very obvious. Summary of the invention
[0009] The first object of the present invention is to provide a method for preparing a layered lithium-rich manganese oxide positive electrode material. This modification method can effectively improve the rate performance of the layered lithium-rich manganese positive electrode material, realize high-current rapid charging and discharging, and further promote the industrialization of the layered lithium-rich manganese positive electrode material. The second object of the present invention is to provide a lithium-ion battery positive electrode using the positive electrode material. The third object of the present invention is to provide a lithium-ion battery using the positive electrode.
[0010] In order to achieve the above-mentioned first purpose, the present invention adopts the following technical solutions:
[0011] A method for preparing a layered lithium-rich manganese oxide positive electrode material, the method comprising the following steps: in the preparation process of a precursor of a lithium-ion battery layered lithium-rich manganese oxide positive electrode material, doping a raw material precursor capable of providing LiCoO2, and then performing a high-temperature heat treatment to obtain the layered lithium-rich manganese oxide positive electrode material.
[0012] The present invention also discloses a layered lithium-rich manganese oxide positive electrode material prepared by any one of the above-mentioned preparation methods.
[0013] In order to achieve the above-mentioned second purpose, the present invention adopts the following technical solution:
[0014] A lithium ion battery positive electrode adopts the layered lithium-rich manganese oxide positive electrode material as the lithium ion battery positive electrode material and mixes it with a conductive agent and then performs ball milling to obtain a mixture, then mixes the mixture with a binder to form a slurry, smears the slurry on an aluminum foil, and dries it to obtain a lithium ion battery positive electrode.
[0015] In order to achieve the third purpose mentioned above, the present invention adopts the following technical solution:
[0016] A lithium ion battery comprises a positive electrode, a negative electrode capable of inserting and removing lithium ions, and an electrolyte between the negative electrode and the positive electrode, wherein the positive electrode is the positive electrode of the lithium ion battery mentioned above.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) The modification method of the present invention has the advantages of being simple, effective, fast, low-cost, highly controllable, and having a wide range of applications;
[0019] (2) The present invention adds an excess of LiCoO2 to the layered lithium-rich manganese, and utilizes the good electrical conductivity of the Co element to effectively improve the electronic conductivity of the lithium-rich manganese positive electrode material, thereby effectively improving its rate performance, greatly improving the large current charge and discharge performance of the layered lithium-rich manganese oxide positive electrode, and realizing large current rapid charge and discharge. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD diagrams of the products of Example 1 of the present invention are compared;
[0021] Figure 2 (a) rate performance curve and (b) rate capacity retention curve of the product of Example 1 of the present invention;
[0022] Figure 3 (a) rate performance curve and (b) rate capacity retention curve of the product of Example 2 of the present invention;
[0023] Figure 4 The XRD diagrams of the products of Example 3 of the present invention are compared;
[0024] Figure 5 (a) rate performance curve and (b) rate capacity retention curve of the product of Example 3 of the present invention;
[0025] Figure 6This is the cycle performance curve of the product of Example 4 of the present invention;
[0026] Figure 7 This is the rate performance curve of the product of Example 4 of the present invention;
[0027] Figure 8 Comparison of high rate cycle performance curves of the product of Example 5 of the present invention;
[0028] Fig. 9 Comparison of high rate cycle performance curves of the product of Example 6 of the present invention;
[0029] Fig.10 Comparison of high rate cycle performance curves of the product of Example 7 of the present invention;
[0030] Fig.11 The high rate cycle performance curves of the product of Example 8 of the present invention are compared. DETAILED DESCRIPTION
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] The first aspect of the present invention provides a method for preparing a layered lithium-rich manganese oxide positive electrode material, which comprises the following steps: in the preparation process of a precursor of a layered lithium-rich manganese oxide positive electrode material for a lithium-ion battery, a raw material precursor capable of providing LiCoO2 is doped, and then a high-temperature heat treatment is performed to obtain the layered lithium-rich manganese oxide positive electrode material.
[0033] The present invention adds a certain amount of LiCoO2 precursor during the preparation process of the layered lithium-rich manganese oxide positive electrode material for lithium-ion batteries to adjust the structure of the layered lithium-rich manganese oxide positive electrode material. Since the Co element has good electrical conductivity, the electronic conductivity of the lithium-rich manganese positive electrode material can be effectively improved, thereby effectively improving its rate performance. The positive electrode and lithium-ion battery using the material belong to the technical field of energy materials and energy conversion. As a positive electrode material for lithium-ion batteries, the material has the advantages of high energy density and good rate performance. The composite material preparation method is simple and suitable for large-scale production.
[0034] According to the present invention, the layered lithium-rich manganese oxide positive electrode material is xLi2MnO3-(1-x)LiMO2, wherein M is selected from at least one of Ni, Co, Mn, Cr and Fe; 0≤x≤1.
[0035] In the layered lithium-rich manganese oxide positive electrode material, 0.1≤x≤0.8. If x is too small or too large, the comprehensive electrochemical performance of the lithium-rich material will decrease. Therefore, x should be selected within a reasonable range.
[0036] Preferably, the amount of the raw material precursor added is such that the molar ratio of the doping amount of LiCoO2 to the layered lithium-rich manganese oxide positive electrode material is 0.01 to 0.7, preferably 0.05 to 0.4. If the doping amount is too little, the modification effect cannot be achieved; if the doping amount is too much, the structure of the original material will be affected, thereby affecting its electrochemical performance.
[0037] Preferably, the precursor is prepared by at least one method selected from a spray method, a coprecipitation method, a sol-gel method, a combustion method, a solid phase method and a molten salt method. The materials obtained by different preparation methods have different phase structures, component distributions, morphologies, particle sizes, etc., which have an important influence on various properties of electrode materials.
[0038] Preferably, the raw materials used in the layered lithium-rich manganese oxide positive electrode material precursor and the raw material precursor of LiCoO2 are independently selected from at least one of acetate, nitrate, sulfate, carbonate, oxalate and metal oxide. Different raw materials have different solubility and melting points, which will have an important impact on the component distribution and phase composition of the synthetic material.
[0039] Preferably, the temperature of the heat treatment is 600-1000°C; the atmosphere of the high temperature heat treatment is at least one of oxygen, air and vacuum; and the heat treatment time is 5-48 hours. The phase structure, component distribution, morphology, particle size, etc. of the materials obtained by different heat treatment temperatures, atmospheres and times are different, which has an important influence on various properties of electrode materials.
[0040] The present invention also discloses a layered lithium-rich manganese oxide positive electrode material prepared by any one of the above-mentioned preparation methods.
[0041] The second aspect of the present invention provides a lithium ion battery positive electrode, which uses the above-mentioned layered lithium-rich manganese oxide positive electrode material as the lithium ion battery positive electrode material, and mixes it with a conductive agent and then performs ball milling to obtain a mixture, and then mixes the mixture and a binder to form a slurry, which is applied on an aluminum foil and dried to obtain a lithium ion battery positive electrode.
[0042] Preferably, the conductive agent is selected from at least one of graphite, acetylene black, Super P, carbon nanotubes, graphene and keratin black.
[0043] Preferably, based on the total weight of the slurry, the content of the conductive agent is 2wt% to 30wt%.
[0044] Preferably, during the ball milling, the mass ratio of the ball to the material is 5:1 to 300:1; the ball milling speed is 100 rpm to 800 rpm; the ball milling time is 0.5 hour to 48 hours; and the ball milling atmosphere is selected from at least one of air, oxygen, nitrogen, hydrogen, argon, carbon dioxide and helium.
[0045] Preferably, the binder is an aqueous binder or a non-aqueous binder known to those skilled in the art, such as at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTEE), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC) and sodium alginate (SA); based on the total weight of the slurry, the amount of the binder is 1wt% to 30wt%.
[0046] A third aspect of the present invention provides a lithium ion battery, comprising a positive electrode, a negative electrode capable of inserting and removing lithium ions, and an electrolyte between the negative electrode and the positive electrode, wherein the positive electrode is the positive electrode of the lithium ion battery described above.
[0047] In the lithium ion battery of the present invention, the negative electrode material can be various conventional negative electrode active materials known to those skilled in the art, such as graphite, silicon and various silicon alloys, iron oxides, tin oxides and various tin alloys, titanium oxides and other negative electrode materials. The electrolyte can be a conventional non-aqueous electrolyte known to those skilled in the art, wherein the lithium salt in the electrolyte can be one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), and lithium fluorohydroxysulfonate (LiC(SO2CF3)3). The non-aqueous solvent can be one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and vinylene carbonate (VC).
[0048] The present invention will be described in detail below by way of examples. In the following examples, the raw materials used in the examples and comparative examples are all commercially available products.
[0049] Example 1
[0050] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2 (LNCMO) cathode material:
[0051] Li, Ni, Co, Mn acetates were added to a certain amount of deionized water according to the stoichiometric ratio, and a uniform reaction solution was obtained by mechanical stirring; then lithium acetate and cobalt acetate were added to the reaction solution according to the molar percentage of LiCoO2 doping (0, 5, 10, 20 mol%); the reaction solution was spray pyrolyzed to obtain a precursor. The obtained precursor was heat treated at 900 degrees Celsius for 10 hours to obtain LiCoO2-doped 0.5Li2MnO3-0.5LiNi 0.33 Co 0.33 Mn 0.33 O2 positive electrode materials, labeled as LiCoO2-0, LiCoO2-5, LiCoO2-10, and LiCoO2-20 respectively.
[0052] The LNCMO-LiCoO2 positive electrode material and the binder were mixed in a certain proportion, and a uniform slurry was obtained by magnetic stirring for 4 hours, and then the slurry was evenly coated on aluminum foil to obtain the electrode material. The characterization battery used a 2025 button cell, and the assembly process was completed in a glove box filled with Ar, and the water and oxygen contents were both less than 0.1ppm. The positive electrode was the prepared electrode sheet; the reference electrode and the counter electrode were metal Li sheets; the diaphragm was Celgard-2400; the electrolyte was LiPF6 (1mol / L) / EC+DEC+EMC (1:1:1), and the assembled battery was placed for testing.
[0053] Figure 1 (a) shows the XRD patterns of LiCoO2-0, LiCoO2-5, LiCoO2-10, and LiCoO2-20 electrode materials. Figure 1 As shown in the figure, all diffraction peaks can correspond well to hexagonal LiMO2 (M = Ni, Co, Mn, etc.) (R-3m) (PDF#85-1966) and monoclinic Li2MO3 (M = Ni, Co, Mn, etc.) (C / 2m) (PDF#84-1634). The diffraction peaks between 20 and 25° (2θ) are characteristic peaks of the Li2MO3 phase, which are caused by the ordered arrangement of LiTM2 in the transition metal (TM) layer in its structure. The "R" and "M" under the diffraction index in the figure represent hexagonal LiMO2 and monoclinic Li2MO3, respectively. In addition, from Figure 1It can be seen from (b) that with the increase of the content of LiCoO2 component, the (002)M characteristic peak of the C / 2m phase in the XRD of the LNCMO positive electrode material gradually weakens, which indicates that increasing the content of LiCoO2 component in LNCMO will reduce its Li2MO3 (M = Ni, Co, Mn, etc.) (C / 2m) content. This is because the crystal structure of the LiCoO2 component is a hexagonal structure of LiMO2 (M = Ni, Co, Mn, etc.) (R-3m). Therefore, increasing the content of LiCoO2 in LNCMO will naturally reduce the content of Li2MO3 (M = Ni, Co, Mn, etc.) (C / 2m) in the structure.
[0054] Figure 2 (a) is the rate performance curve of LiCoO2-0, LiCoO2-5, LiCoO2-10, and LiCoO2-20 electrode materials, and their rate capacity retention rates at different rates are shown in Figure 2. Figure 2 (b). The results show that below 1C rate, LiCoO2-0 electrode material shows a higher rate capacity, while when the charge and discharge rate is ≥1C, LiCoO2-5, LiCoO2-10, and LiCoO2-20 electrode materials show relatively high rate capacity. At a high rate of 10C, the discharge rate capacity of LiCoO2-20 electrode material is 143 mAh / g, while the discharge rate capacity of LiCoO2-0 electrode material is only 130 mAh / g. The results show that increasing the content of LiCoO2 component can improve the high rate performance of LNCMO positive electrode material.
[0055] Example 2
[0056] Preparation of LiCoO2 doped with 0.7Li2MnO3-0.3LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2(LNCMO-1) positive electrode material.
[0057] Li, Ni, Co, and Mn acetates were added to a certain amount of deionized water according to the stoichiometric ratio, and a uniform reaction solution was obtained by mechanical stirring; then lithium acetate and nickel acetate were added to the reaction solution according to the molar percentage of LiCoO2 added (0, 5, 10, 20 mol%); the reaction solution was spray pyrolyzed to obtain a precursor. The obtained precursor was heat treated at 900 degrees Celsius for 10 hours to obtain LiCoO2-doped LNCMO-1 positive electrode materials, which were marked as LiCoO2-1-0, LiCoO2-1-5, LiCoO2-1-10, and LiCoO2-1-20.
[0058] The preparation of electrode materials and battery assembly are the same as in Example 1.
[0059] Figure 3 (a) is the rate performance curve of LiCoO2-1-0, LiCoO2-1-5, LiCoO2-1-10, and LiCoO2-1-20 electrode materials, and their rate capacity retention rates at different rates are shown in Figure 2. Figure 3 (b). As shown in the figure, increasing the LiCoO2 content can effectively improve the rate performance of the LNCMO-1 positive electrode material. The results show that below the 1C rate, the LiCoO2-0 electrode material shows a higher rate capacity, while when the charge and discharge rate is ≥1C, the LiCoO2-1-5, LiCoO2-1-10, and LiCoO2-1-20 electrode materials show relatively high rate capacity. When at a high rate of 10C, the discharge rate capacity of the LiCoO2-1-20 electrode material is 145.6 mAh / g, while the discharge rate capacity of the LiCoO2-1-0 electrode material is only 127.7 mAh / g. The results show that increasing the LiCoO2 component content can improve the high rate performance of the LNCMO-1 positive electrode material.
[0060] Example 3
[0061] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2 positive electrode material-nitrate.
[0062] Li, Ni, Co, and Mn nitrates are added to a certain amount of deionized water according to a stoichiometric ratio, and a uniform reaction solution is obtained by mechanical stirring; then lithium nitrate and nickel nitrate are added to the reaction solution according to the molar percentage of LiCoO2 (0, 5, 10, 20 mol%); the reaction solution is spray pyrolyzed to obtain a precursor. The obtained precursor is heat-treated at 900 degrees Celsius for 10 hours to obtain LiCoO2-doped LNCMO positive electrode materials, which are marked as LiCoO2-2-0, LiCoO2-2-5, LiCoO2-2-10, and LiCoO2-2-20.
[0063] The electrode preparation and battery assembly were the same as in Example 1.
[0064] Figure 4 The following are the XRD patterns of LiCoO2-2-0, LiCoO2-2-5, LiCoO2-2-10 and LiCoO2-2-20 electrode materials. Figure 4As shown in Figure 1, all diffraction peaks can correspond well to hexagonal LiMO2 (M = Ni, Co, Mn, etc.) (R-3m) (PDF#85-1966) and monoclinic Li2MO3 (M = Ni, Co, Mn, etc.) (C / 2m) (PDF#84-1634). Figure 4 It can be seen that with the increase of LiCoO2 component content, the (002)M characteristic peak of the C / 2m phase in the XRD of the LNCMO positive electrode material gradually weakens, which indicates that increasing the content of LiCoO2 component in LNCMO will reduce its Li2MO3 (M=Ni, Co, Mn, etc.) (C / 2m) content. This is because the crystal structure of the LiCoO2 component is a hexagonal structure of LiMO2 (M=Ni, Co, Mn, etc.) (R-3m). Therefore, increasing the content of LiCoO2 in LNCMO will naturally reduce the content of Li2MO3 (M=Ni, Co, Mn, etc.) (C / 2m) in the structure.
[0065] Figure 5 (a) is the rate performance curve of LiCoO2-2-0, LiCoO2-2-5, LiCoO2-2-10, and LiCoO2-2-20 electrode materials. Figure 5 (b) shows that increasing the LiCoO2 component content can improve the rate retention rate of the LNCMO positive electrode material and improve the rate performance of the LNCMO positive electrode material.
[0066] Example 4
[0067] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2(LNCMO) cathode material-different heat treatment temperatures.
[0068] Li, Ni, Co, and Mn nitrates are added to a certain amount of deionized water according to a stoichiometric ratio, and a uniform reaction solution is obtained by mechanical stirring; then lithium nitrate and cobalt nitrate are added to the reaction solution according to the molar percentage of LiCoO2 (20 mol%); the reaction solution is spray pyrolyzed to obtain a precursor. The obtained precursor is heat-treated at 400, 500, 600, 700, 800, 900, 1000, and 1100 degrees Celsius for 10 hours to obtain LiCoO2-doped LNCMO positive electrode materials.
[0069] The electrode preparation and battery assembly were the same as in Example 1.
[0070] Figure 6The cycle performance curves of LNCMO cathode materials with different heat treatment temperatures show that the heat treatment temperature has a great influence on the cycle stability and cycle capacity of LNCMO cathode materials. At a current density of 20 mA / g, after 40 cycles, the discharge specific capacities of LNCMO cathode materials with different heat treatment temperatures are 69.8, 145.9, 182.2, 212.9, 215.3, 277.4, 214.8, and 175.4 mA / g, respectively; and the capacity retention rates are 36.8, 66.9, 77.1, 83.4, 90.6, 96.2, 80.4, and 83.3%, respectively. The results show that the LNCMO cathode material obtained by heat treatment at 900 degrees Celsius has the highest cycle capacity.
[0071] Figure 7 Figure 2 is the rate performance curve of LNCMO cathode material at different heat treatment temperatures. As can be seen from the curve, as the cycle progresses, from 400℃ to 900℃, the rate capacity of LNCMO cathode material increases with the increase of heat treatment temperature, and its rate capacity retention rate also gradually increases; when the heat treatment temperature is further increased to 1000℃ and 1100℃, its rate capacity gradually decreases. Therefore, the LNCMO cathode material obtained by heat treatment at 900℃ has the best rate performance. From 400℃ to 900℃, the rate capacity of LNCMO cathode material increases with the increase of heat treatment temperature because within this temperature range, with the increase of temperature, it is easier to form a more complete layered lithium-rich manganese phase, which increases its reversible capacity and rate characteristics during the cycle, thereby improving the rate capacity of LNCMO cathode material. When the heat treatment temperature is further increased to 1000℃ and 1100℃, its rate capacity gradually decreases, which may be mainly affected by the particle size of LNCMO cathode material.
[0072] Example 5
[0073] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2 (LNCMO) positive electrode material.
[0074] Li, Ni, Co, and Mn acetates are added to a certain amount of deionized water according to the stoichiometric ratio, and a uniform reaction solution is obtained by mechanical stirring; then lithium acetate and nickel acetate are added to the reaction solution according to the molar percentage of LiCoO2 doping (0, 5, 10, 20 mol%); the reaction solution is spray pyrolyzed to obtain a precursor. The obtained precursor is heat-treated at 900 degrees Celsius in an oxygen atmosphere for 10 hours to obtain a LiCoO2-doped LNCMO positive electrode material.
[0075] The electrode preparation and battery assembly were the same as in Example 1.
[0076] Figure 8 It shows that increasing the LiCoO2 component content can improve the rate performance of LNCMO cathode materials and increase the high capacity under large current.
[0077] Example 6
[0078] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by spray pyrolysis 0.33 Co 0.33 Mn 0.33 O2 (LNCMO) positive electrode material.
[0079] Li, Ni, Co, and Mn acetates are added to a certain amount of deionized water according to the stoichiometric ratio, and a uniform reaction solution is obtained by mechanical stirring; then lithium acetate and nickel acetate are added to the reaction solution according to the molar percentage of LiCoO2 doping (0, 5, 10, 20 mol%); the reaction solution is spray pyrolyzed to obtain a precursor. The obtained precursor is heat-treated at 900 degrees Celsius in an air atmosphere for 48 hours to obtain a LiCoO2-doped LNCMO positive electrode material.
[0080] The electrode preparation and battery assembly were the same as in Example 1.
[0081] Fig. 9 It shows that increasing the LiCoO2 component content can improve the rate performance of LNCMO cathode materials and increase the high capacity under large current.
[0082] Example 7
[0083] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by sol-gel method 0.33 Co 0.33 Mn 0.33 O2 (LNCMO) positive electrode material.
[0084] Li, Ni, Co, and Mn acetates were added to a certain amount of ethanol solution according to the stoichiometric ratio, and then lithium acetate and nickel acetate were added to the reaction solution according to the molar percentage of LiCoO2 doping (20 mol%), magnetic stirring was performed until the sol was formed, and then drying was performed at 120 degrees Celsius for 12 hours to obtain a gel precursor. The obtained precursor was heat treated at 900 degrees Celsius for 10 hours to obtain LNCMO positive electrode materials doped with different LiCoO2.
[0085] The preparation of electrodes and the assembly of the battery are the same as in Example 1.
[0086] Fig.10The cycle performance curve of LNCMO prepared by sol-gel method and 20% molar percentage LiCoO2 doped positive electrode material at 200 mA / g current density. The results show that LiCoO2 doping can effectively improve the rate performance and cycle stability under high current.
[0087] Example 8
[0088] Preparation of LiCoO2 doped with 0.5Li2MnO3-0.5LiNi by coprecipitation method 0.33 Co 0.33 Mn 0.33 O2 (LNCMO) positive electrode material.
[0089] Li, Ni, Co, and Mn acetates are added to a certain amount of deionized water solution according to a stoichiometric ratio, and then lithium acetate and nickel acetate are added to the reaction solution according to the molar percentage of LiCoO2 doping (20 mol%), and the pH value is adjusted to 10 with ammonia water. The reaction solution is mechanically stirred for 10 hours until the reactant precipitates, and then the reaction solution is removed by suction filtration, and the product is dried at 120 degrees Celsius for 12 hours to obtain a precursor. The obtained precursor is heat-treated at 900 degrees Celsius for 10 hours to obtain LNCMO positive electrode materials doped with different LiCoO2.
[0090] The preparation of electrodes and the assembly of the battery are the same as in Example 1.
[0091] Fig.11 The cycle performance curve of LNCMO prepared by coprecipitation method and 20% molar percentage LiCoO2 doped positive electrode material at 200 mA / g current density. The results show that LiCoO2 doping can effectively improve the rate performance and cycle stability under high current.
[0092] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a layered lithium-rich manganese oxide positive electrode material, characterized in that: The method comprises the following steps: in the process of preparing a precursor of a lithium-ion battery layered lithium-rich manganese oxide positive electrode material, doping a raw material precursor capable of providing LiCoO2, and then performing a high-temperature heat treatment to obtain a layered lithium-rich manganese oxide positive electrode material; The amount of the raw material precursor added is such that the molar ratio of the doping amount of LiCoO2 to the layered lithium-rich manganese oxide positive electrode material is 0.05-0.2; The heat treatment temperature is 400-900°C and the heat treatment time is 10-50 hours; The layered lithium-rich manganese oxide positive electrode material is xLi2MnO3-(1-x)LiMO2, wherein M is selected from at least one of Ni, Co, Mn, Cr and Fe; 0.1≤x≤0.
8.
2. The preparation method according to claim 1, characterized in that: The preparation method of the lithium-ion battery layered lithium-rich manganese oxide positive electrode material precursor is selected from at least one of a spray method, a coprecipitation method, a sol-gel method, a combustion method, a solid phase method and a molten salt method.
3. The preparation method according to claim 1, characterized in that: The atmosphere of the high temperature heat treatment is at least one of oxygen, air and vacuum.
4. The preparation method according to claim 1, characterized in that: The raw materials used for the layered lithium-rich manganese oxide positive electrode material precursor and the raw material precursor of LiCoO2 are independently selected from at least one of acetate, nitrate, sulfate, carbonate, oxalate and metal oxide.
5. A layered lithium-rich manganese oxide positive electrode material prepared by the method according to any one of claims 1 to 4.
6. A lithium ion battery positive electrode, characterized in that: The positive electrode material according to claim 5 is used as the positive electrode material, and is mixed with a conductive agent and then ball-milled to obtain a mixture, and then the mixture and a binder are mixed to form a slurry, and the slurry is applied on an aluminum foil and dried to obtain a lithium-ion battery positive electrode.
7. The lithium-ion battery positive electrode according to claim 6, characterized in that: The conductive agent is selected from at least one of graphite, acetylene black, Super P, carbon nanotubes, graphene and keratin black; Based on the total weight of the slurry, the content of the conductive agent is 2wt%~30wt%.
8. The lithium ion battery positive electrode according to claim 6 or 7, characterized in that: The binder is selected from at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, styrene-butadiene rubber, sodium carboxymethyl cellulose and sodium alginate; Based on the total weight of the slurry, the amount of the binder is 1wt%~30wt%.
9. The lithium-ion battery positive electrode according to claim 6, characterized in that: The ball milling steps include: a ball-to-material mass ratio of 5:1 to 300:1; a ball milling speed of 100 to 800 rpm; a ball milling time of 0.5 to 48 hours; and a ball milling atmosphere selected from at least one of air, oxygen, nitrogen, hydrogen, argon, carbon dioxide and helium.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode capable of inserting and extracting lithium ions, and an electrolyte between the negative electrode and the positive electrode, wherein the positive electrode is the positive electrode of the lithium-ion battery according to any one of claims 6 to 9.
Citation Information
Patent Citations
Layered lithium-rich manganese oxide positive electrode material suppressing capacity / voltage attenuation during circulation process effectively and preparation method therefor and application thereof
CN107069026A